Developing Mathematics Learning Model of Thinking Empowerment by Question (TEQ) with TAI Setting to Improve Students Metacognition Ability - Khasanah, Uswatun; Astuti, Dwi (International Journal of Active Learning, 2018)
The method used in the development of mathematics learning model of Thinking Empowerment by Question (TEQ) with TAI setting is R & D through 4-D steps, i.e., define, design, develop and disseminate. The subjects in the implementation of the model are the seventh-grade students of one of the junior high schools in Yogyakarta in the academic year 2017/2018 on the plane material. The method used in the model implementation is the quasi-experimental one group pretest-posttest design. Metacognition ability obtained used closed questionnaire. This model is based on the value of count proven to improve students' metacognition ability.